2018
DOI: 10.1128/msphere.00471-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Engineered Expression of Mitochondrial Association Factor 1b onToxoplasma gondiiInfection and the Host Response in a Mouse Model

Abstract: The parasite Toxoplasma gondii currently infects approximately one-third of the world’s population and causes life-threatening toxoplasmosis in individuals with undeveloped or weakened immune systems. Current treatments are unable to cure T. gondii infection, leaving infected individuals with slow-growing tissue cysts for the remainder of their lives. Previous work has shown that expression of the parasite protein mitochondrial association factor 1 (MAF1b) is responsible for the association of T. gondii parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Cysts are also strongly associated with ER, Golgi complex and endolysosomal vesicles, while host mitochondria were not observed near the cyst membrane. Notably, type II strains are not able to recruit mitochondria to the vicinity of the PVM (Paredes-Santos et al, 2017) due to a lack of expression of the dense granule protein MAF-1b (Pernas et al, 2014; English and Boyle, 2018). Even though the proximity of host organelles with the cyst wall was demonstrated, it is not known if this organization around the cyst is related to nutrient acquisition by bradyzoites.…”
Section: Introductionmentioning
confidence: 99%
“…Cysts are also strongly associated with ER, Golgi complex and endolysosomal vesicles, while host mitochondria were not observed near the cyst membrane. Notably, type II strains are not able to recruit mitochondria to the vicinity of the PVM (Paredes-Santos et al, 2017) due to a lack of expression of the dense granule protein MAF-1b (Pernas et al, 2014; English and Boyle, 2018). Even though the proximity of host organelles with the cyst wall was demonstrated, it is not known if this organization around the cyst is related to nutrient acquisition by bradyzoites.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that mROS also played a role in parasite restriction is in keeping with several studies that have shown that mROS plays an important role in macrophage killing of phagosomally localized bacteria ( 46 , 47 ) and extends this work to suggest that mROS may play in important role in pathogen defense in nonimmune cells as well. This finding is especially interesting given that type I and III strains, but not type II strains, show high levels of host mitochondrion association with the PV, the host membrane-derived structure, which surrounds intracellular parasites and avoids fusion with the phagolysosome ( 50 59 ). Host mitochondria associating with the PV might be able to deliver mitochondrion-derived vesicles harboring ROS ( 47 ) to the underlying parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The associating mitochondria may also be somewhat dysfunctional (Syn et al., 2017). Regardless of which impact is most important, the data are clear that this association is of substantial importance in vivo during the acute and, possibly, chronic stages of the infection (English & Boyle, 2018).…”
Section: Maf1 Is a Pvm‐associating Effector That Mediates Associationmentioning
confidence: 99%